Tingkat Pengetahuan Pranikah tentang Imunisasi TT (Tetanus Toxoid) di Wilayah Kerja Puskesmas Bestari Medan Petisah Tahun 2023 - Adriana Bangun; Sabariana Tarigan; Putri Nadila; Revina Untari; Shafira Elzahra (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
According to WHO (2015), TT immunization coverage in Africa reached 50%, with TT2 at 60%. In Indonesia, the Making Pregnancy Safer (MPS) program set a target of 95% Antenatal Care (K1) coverage, including TT2 by 2019. Puskesmas data in 2016 showed K1 coverage of 880 with TT1 at 27 (3.1%), and K4 at 739 with TT2 at 64 (8.6%). This study aims to assess premarital knowledge of TT immunization based on age, education, and occupation. Using a descriptive design and total sampling, 32 respondents were involved. Results showed most were under 20 years old (41%), had junior high school education (25%), and worked as entrepreneurs (19%). The lowest knowledge level was found among respondents with primary education (19%) and farmers (3%). It is recommended that midwives at Puskesmas Bestari intensify education to improve premarital knowledge about TT immunization.